2022
DOI: 10.1007/s12553-022-00711-5
|View full text |Cite
|
Sign up to set email alerts
|

CNN-LSTM deep learning based forecasting model for COVID-19 infection cases in Nigeria, South Africa and Botswana

Abstract: Background COVID-19 pandemic has indeed plunged the global community especially African countries into an alarming difficult situation culminating into a great deal amounts of catastrophes such as economic recession, political instability and loss of jobs. The pandemic spreads exponentially and causes loss of lives. Following the outbreak of the omicron new variant of concern, forecasting and identification of the COVID-19 infection cases is very vital for government at various levels. Hence, having knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our findings are consistent with prior conclusions drawn by Muhammad LJ et al (23) and Zhang, J et al (25). In additional, our LSTM and CNN-LSTM models leveraged a unique memory mechanism, prioritizing data points closer to the present moment in the prediction process.…”
Section: Cnn Lstm and Cnn-lstm Modelssupporting
confidence: 90%
“…Our findings are consistent with prior conclusions drawn by Muhammad LJ et al (23) and Zhang, J et al (25). In additional, our LSTM and CNN-LSTM models leveraged a unique memory mechanism, prioritizing data points closer to the present moment in the prediction process.…”
Section: Cnn Lstm and Cnn-lstm Modelssupporting
confidence: 90%
“…For example, Mumtaz et al 31 used ARIMA to predict the daily confirmed cases in European countries, while Yesilkanat 32 used a Random Forest model to predict the number of cases and deaths. Muhammad et al 33 used a CNN-LSTM model to predict the number of confirmed cases and deaths in Nigeria, South Africa, and Botswana. We summarize a list of recent work from year 2020 to 2022 in Table 1 .…”
Section: Introductionmentioning
confidence: 99%